Carbon dioxide and methane emission from compacted tropical peat soil - Busman, Nur Azima (2019)
Tropical peatland stores a large amount of carbon (C) and is an important C sink. In Malaysia, 25% of the peatland area has been converted to oil palm plantation where drainage, compaction and groundwater table control are pre-requisite. To date, relationship between land compaction and C emission from tropical peatland is limited. To understand the effect of compaction on soil C emission from tropical peatland, a laboratory soil column incubation study was conducted. Peat soil used in this study was classified as hemist and collected from a Mixed Peat Swamp forest. Soil were then packed and compacted in columns made of polyvinyl chloride (PVC) pipes to three different soil bulk densities (BD); 0.14, 0.18 and 0.22 g cm⁻³. Soil CO₂ flux, CH4 flux, DOC concentration and soil redox potential (Eh) from the soil columns were measured weekly for 12 weeks. Total soil porosity and moisture retention of each soil BD at field capacity were also determined using another set of peat sample packed into 100 cm³ soil core ring. Field measurement of soil CO₂ flux and CH4 flux at oil palm plantation, where the soil BD ranges from 0.20 to 0.24 g cm⁻³ were also monitored for one year for comparison and validation against the soil column approach using result from BD 0.22 g cm⁻³. Soil porosity decreased while moisture retention increased proportionally with increasing soil BD. Total porosity was greater for BD 0.14 (91%), followed by BD 0.18 (87%) and BD 0.22 (83%). In contrast, volumetric moisture content at field capacity were greater at soil BD 0.22 (80%), followed by 0.18 (74%) and 0.14 (64%). Results from soil column incubation showed that soil CO₂ fluxes were greater for compacted peat and tend to increase when water infiltration become slower with time, until when the soil is at or near the saturation point, soil water content becomes a limiting factor for soil CO₂ fluxes. On contrary, CH4 fluxes were not affected by the changes in water infiltration rates and compaction reduced soil CH4 fluxes by about 22%. Total CH4 flux for 12 weeks incubation was highest at soil BD 0.14 (461 mg C m⁻²) followed by BD 0.22 (363 mg C m⁻²) and BD 0.18 (360 mg C m⁻²). Total DOC concentration also significantly higher by almost two times at soil BD 0.14 (8588 mg L⁻¹) compared to soil compacted to BD 0.18 (4912 mg L⁻¹) and BD 0.22 (4930 mg L⁻¹). Soil Eh which act as indirect indicator for the oxygenation status, shows no significant correlations with both CO₂ flux (r=0.16–0.45) and CH₄ flux (r=0.01–0.24). This study indicated that the modification of physical properties (like soil porosity and moisture retention) after compaction affects the water movement and gaseous transport in the soil profile, thus influences the C emission from peat soil. However, further improvement on the experimental soil column set-up are required as comparison with in-situ field monitoring showed that CO₂ fluxes from soil column incubation were slightly smaller than the field measurement.